Development and validation of the quality care questionnaire –palliative care (QCQ-PC): patient-reported assessment of quality of palliative care - Young Ho Yun (BMC Palliative Care, 2018)
Abstract Background In this study, we aimed to develop and validate an instrument that could be used by patients with cancer to evaluate their quality of palliative care. Methods Development of the questionnaire followed the four-phase process: item generation and reduction, construction, pilot testing, and field testing. Based on the literature, we constructed a list of items for the quality of palliative care from 104 quality care issues divided into 14 subscales. We constructed scales of 43 items that only the cancer patients were asked to answer. Using relevance and feasibility criteria and pilot testing, we developed a 44-item questionnaire. To assess the sensitivity and validity of the questionnaire, we recruited 220 patients over 18 years of age from three Korean hospitals. Results Factor analysis of the data and fit statistics process resulted in the 4-factor, 32-item Quality Care Questionnaire-Palliative Care (QCQ-PC), which covers appropriate communication with health care professionals (ten items), discussing value of life and goals of care (nine items), support and counseling for needs of holistic care (seven items), and accessibility and sustainability of care (six items). All subscales and total scores showed a high internal consistency (Cronbach alpha range, 0.89 to 0.97). Multi-trait scaling analysis showed good convergent (0.568–0.995) and discriminant (0.472–0.869) validity. The correlation between the total and subscale scores of QCQ-PC and those of EORTC QLQ-C15-PAL, MQOL, SAT-SF, and DCS was obtained. Conclusion This study demonstrates that the QCQ-PC can be adopted to assess the quality of care in patients with cancer.